Detection and quantification of mature circulating endothelial cells using flow cytometry and immunomagnetic beads: a methodological comparison - Goon, Patrick K Y; Boos, Christopher J; Stonelake, Paul S; Blann, Andrew D; Lip, Gregory Y H (Thrombosis and haemostasis, 2006)
Mature circulating endothelial cells (CECs) are novel cellular markers of endothelial damage/dysfunction. The two main techniques of CEC enumeration are flow cytometry (FC) and immunomagnetic bead (IB) isolation. Both quantify CECs accurately, but a direct comparison of both methods has not been reported. We sought to assess the agreement between the two methods in two patient populations, and a group of healthy subjects, with emphasis given to methodological issues. We included 34 patients with acute coronary syndrome (ACS), 60 patients with primary breast cancer (PBC) and 30 healthy controls (HC). We quantified CECs using the IB method [CD146 and FITCUlex europaeus lectin-1] and FC [CD45, CD34 and CD146]. Bland-Altman plots suggested reasonable agreement (<5% of events >2 standard deviations from the mean) between FC and the IB methods for CEC quantification in whole blood in the two disease groups (ACS and PBC), but not among the HCs. There were no statistically significant differences in CEC levels by the two methods amongst all three patient groups. There is reasonable agreement between the FC and the IB methods for mature CEC quantification in whole blood, especially amongst disease groups. The agreement between the two methods appears to weaken in healthy controls, and at lower and higher absolute CEC counts.